adquisiciones y donaciones. - Museo de Bellas Artes Caracas (Caracas : Museo de Bellas Artes, 1963)
Bertoia, Harry ; Cabre, Manuel ; Calder, Alexander ; Cuevas, Jose Luis ; Chab, Victor ; Deira, Ernesto ; Dodeigne, Eugene ; Egas, Camilo ; Fernandez Muro, Jose A. ; Gonzalez, Pedro Angel ; Grillo, Sarah ; Lam, Wilfredo ; Mabe, Manabu ; Maccio, Romulo ; Mata, Roberto ; Merida, Carlos ; etc.
adquisiciones y donaciones, Museo de Bellas Artes, Caracas, 12 mayo, 1963
boek